1997
DOI: 10.1111/j.1365-2214.1997.tb00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet, smoking and exercise: interrelationships between adolescent health behaviours

Abstract: A questionnaire measuring smoking status, exercise and dietary behaviour was administered to 932 high school pupils during regular classroom periods. Pupils were taken from three year groups which included 327 year 8 (12-13 years), 313 year 9 (13-14 years) and 292 year 10 (14-15 years). Pupils also indicated whether they could recall classroom teaching on 15 food- and health-related issues. Scores were derived representing self-reported frequency of eating foods that were high in fat, and fresh fruits and vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…Relationships between diet and physical activity have been demonstrated in cross-sectional studies in adults [11][12][13][14][15][16] and youth [9,[17][18][19][20][21] but there is less known about the covariation of these behaviors over time [22]. One study examined cross-sectional relationships between healthy eating behaviors and physical activity over 7 years in individuals from 6 th to 12 th grades, some of whom were part of a health behavior intervention [9] .…”
mentioning
confidence: 97%
“…Relationships between diet and physical activity have been demonstrated in cross-sectional studies in adults [11][12][13][14][15][16] and youth [9,[17][18][19][20][21] but there is less known about the covariation of these behaviors over time [22]. One study examined cross-sectional relationships between healthy eating behaviors and physical activity over 7 years in individuals from 6 th to 12 th grades, some of whom were part of a health behavior intervention [9] .…”
mentioning
confidence: 97%
“…Similar findings have been previously reported by Coulson and colleagues. 15 Studies in adults also report less healthy diets in smokers compared to non-smokers. A meta-analysis of over 60 studies in adults examining patterns of nutrient intake in smokers revealed a slight increase in total calories and fat among smokers as well as decreased intake of fiber, fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether this effect was due to smoking itself or due to correlates of a lifestyle which includes smoking (such as reduced exercise [32,33]), resting heart rates were compared between smokers and non-smokers separately for those groups which included exercise in their regular habits, and those who did not.…”
Section: Resultsmentioning
confidence: 99%